O Brasil na exposi????o universal de Xangai: dimens??o intercultural e discurso imag??tico - Barbosa, Ana Claudia Cunha (2013)
This master's thesis is a reflection on how Brazil has shaped its speech to the Chinese in the context of a large cultural meeting held in Shanghai, where economic interests has influenced in the structure of the message. To conduct the study, it became essential to consider the interface between globalization, image and interculturality. However, the otherness emerged as a essential theme in the integration of these three topics, since we perceive as the core element of the discursive construction of the country, as well as the impact of the cultural distance between sender and receier. In this respect, the research examines the paradox between the ascendancy of the stereotype and the pretension of a symbolic enhanced process. Several authors helped to build the theoretical basis of the study, especially Todorov, Bakhtin, Canclini. The semiotics of culture was the main methodology used in this work, but we also rely on anthropological concepts of Gilbert Durand. With this master's thesis we aim to help Brazil on its discursive conception in international events, where the country is gathering further highlight.